1999
DOI: 10.4319/lo.1999.44.7.1781
|View full text |Cite
|
Sign up to set email alerts
|

Critical depth and critical turbulence: Two different mechanisms for the development of phytoplankton blooms

Abstract: A turbulent diffusion model shows that there are two different mechanisms for the development of phytoplankton blooms. One of these mechanisms works in well‐mixed environments and corresponds to the classical critical depth theory. The other mechanism is based on the rate of turbulent mixing. If turbulent mixing is less than a critical turbulence, phytoplankton growth rates exceed the vertical mixing rates, and a bloom develops irrespective of the depth of the upper water layer. These results demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
364
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 435 publications
(385 citation statements)
references
References 35 publications
17
364
2
2
Order By: Relevance
“…Several field studies have shown that certain environmental factors are associated with the amount of toxins found in cyanobacterial blooms (Wicks and Thiel, 1990;Zheng et al, 2004). A wide range of laboratory studies also have examined the effects of various environmental factors on microcystin production, including trace metal supply (Lukac and Aegerter, 1993;Utkilen and Gjølme, 1995), nitrogen and phosphorus (Sivonen, 1990), light and temperature (van der Westhuizen and Eloff, 1985), pH (de Maagd et al, 1999), culture medium (Song et al, 1998), water column stability (Huisman et al, 1999) and grazing pressure by zooplankton (Paerl, 1996;Hyenstrand et al, 1998). However, there are still many controversial issues from both field and laboratory studies on the mechanisms of microcystin production.…”
Section: Introductionmentioning
confidence: 99%
“…Several field studies have shown that certain environmental factors are associated with the amount of toxins found in cyanobacterial blooms (Wicks and Thiel, 1990;Zheng et al, 2004). A wide range of laboratory studies also have examined the effects of various environmental factors on microcystin production, including trace metal supply (Lukac and Aegerter, 1993;Utkilen and Gjølme, 1995), nitrogen and phosphorus (Sivonen, 1990), light and temperature (van der Westhuizen and Eloff, 1985), pH (de Maagd et al, 1999), culture medium (Song et al, 1998), water column stability (Huisman et al, 1999) and grazing pressure by zooplankton (Paerl, 1996;Hyenstrand et al, 1998). However, there are still many controversial issues from both field and laboratory studies on the mechanisms of microcystin production.…”
Section: Introductionmentioning
confidence: 99%
“…Stratification suppresses turbulence and reduces the mixed layer depth, thereby relaxing light limitation but at the same time restricting the flow of nutrients from depth (Mahadevan et al 2012). In temperate and high latitude regions, the annual establishment of seasonal stratification often triggers the highly productive phytoplankton spring bloom (Sverdrup 1953;Huisman et al 1999;Siegel et al 2002). However, strong and prolonged stratification often leads to ocean oligotrophication as phytoplankton become nutrient limited by depletion of the nutrients in the surface layer.…”
mentioning
confidence: 99%
“…There are competing hypotheses to explain phytoplankton bloom phenology (timing and intensity), including the "dilution recoupling hypothesis" or "disturbance recovery hypothesis" (Behrenfeld, 2010;Boss and Behrenfeld, 2010) and the "critical turbulence hypothesis" (Brody and Lozier, 2015;Huisman et al, 1999;Taylor and Ferrari, 2011).…”
Section: Caveats and Limitationsmentioning
confidence: 99%